Media Sosial (Instagram dan Facebook) terhadap Promosi Pemasaran - Muhamad Effendi; Murlina Nisusmiati; Rudi Azhar; Riski Amelia (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of the use of social media (Instagram and Facebook) on marketing promotions at JNE express Lubuklinggau goods delivery services. This research method is descriptive research with a quantitative approach. Distribution of questionnaires used to obtain data. The questionnaire uses a Likert scale as a form of assessment. Data analysis techniques were carried out using descriptive statistical analysis and inferential statistical analysis. The results showed, a) the Instagram social media use variable had a T count (3.242) more than T table (1.986); b) social media use variable Facebook has a T count (3.452) more than T table (1.986); c) the variable value of F count is 20.913 more than F table (2.71). In conclusion, partially the use of Instagram and Facebook social media has a significant effect on Marketing Promotion at JNE Lubuklinggau. The simultaneous use of Instagram Social Media and Facebook Social Media Use has a significant effect on Marketing Promotion at JNE Lubuklinggau. Keywords: Use of Facebook Social Media, Use of Instagram Social Media, Marketing Promotion